Effect of Temperature on Oscillatory Behaviour of the System Containing Isomers of Hydroxybenzoic Acid in Batch Reactor - Masood A. Nath; Nadeem B. Ganaie; R. P. Rastogi; G. M. Peerzada (E-Journal of Chemistry)
In the present paper a thorough study of temperature dependence on oscillatory behaviour of the Belousov-Zhabotinsky (BZ) system containing the isomers of hydroxybenzoic acids + BrO3-+ Mn(II) in aqueous acid medium (1.0 M H2SO4) at a fixed concentration of reacting species has been reported. On varying temperature, the oscillatory parameters like induction time, time period and number of oscillations show marked changes. These changes arise due to the position and number of hydroxyl groups in these isomers which affect the oscillations. Experimental observations have satisfactorily been explained by FKN mechanism and kinetic parameters. The oscillatory characteristics depend on the temperature dependence of the rate constant of the reaction controlling the inhibitory reaction steps (negative feedback)